The Intervention of Slow-Stroke Back Massage Cutaneous Stimulus Techniques in Patients with Rheumatoid Arthritis - Yessy Aprihatin; Linda Andriani; Erpita Yanti (Jurnal Penelitian Pendidikan IPA, 2023)
Rheumatoid Arthritis (RA) is the highest order of disease in the elderly in Indonesia in 2020 where with a percentage value of 49% and this disease occurs more frequently in women than in men. Treatment of pain in RA patients can be done with pharmacological therapy and non-pharmacological therapy. The aim of the study was to respondentâ€™s intervention technic slow-stroke back massage cutaneous stimulus pada patient RA patients in the working area of the Pariaman Health Center. This research is a quantitative type using a quasi-experimental research design method. In this study design, there was an intervention group without a control group. Research design approach with one group pretest-posttest. The conclusion obtained in this study was that RA elderly respondents in the working area of the Pariaman Health Center were the female sex was 16 respondents (53.30%), and the male sex was 14 respondents (46.70%). The RA elderly pain scale before being given Kutaneus Slow-Stroke Back Massage therapy in the working area of the Pariaman Health Center, namely 26 respondents (86.70%) experienced moderate pain and 4 respondents (13.30%) experienced mild pain. Pain scale in elderly RA after being given Kutaneus Slow-Stroke Back Massage therapy in the working area of the Pariaman Health Center, namely 16 respondents (53.30%) experienced mild pain and 14 respondents (46.70%) experienced moderate pain. Â